PI-RADS v2 Findings of MRI and Positive Biopsy Core Percentage would Predict Pathological Extraprostatic Extension in Patients who Underwent Robot Assisted Radical Prostatectomy: A Retrospective Study - Yamashita, Shimpei; Kohjimoto , Yasuo; Sato , Hirotatsu; Kikkawa , Kazuro; Sonomura, Tetsuo; Hara, Isao (Urology Journal, 2022)
Purpose: This study aimed to examine whether preoperative Prostate Imaging Reporting and Data System v2 (PI-RADS v2) can predict pathological extracapsular extension (EPE) after radical prostatectomy. We also studied the preoperative factors which can predict EPE. Materials and Methods: In our institute, 294 patients underwent robot assisted radical prostatectomy (RARP) between December 2012 and August 2016. In this era, we performed MRI after biopsy to determine clinical stage before surgery. PI-RADS v2 scores were retrospectively reviewed using biparametric MRI and EPE in pathological mapping of resected specimens for each lobe. Results: In the excised specimen, EPE was observed in 73 lobes (12%). The percentage of EPE by PI-RADS v2 score was score ‘1’: 6% (17/297 lobes), ‘2’: 3% (1/33 lobes), ‘3’: 12% (8/67 lobes), ‘4’: 19% (27/139 lobes), and ‘5’: 38% (20/52 lobes). The higher the PI-RADS score, the higher the percentage of EPE (P <0.01). When classified as PI-RADS score ≥4 and <4, the positive predictive value (PPV) was 24.6% (47/191 lobes, 95%CI: 0.187 – 0.313) and negative predictive value (NPV) was 93.5% (371/397 lobes, 95%CI: 0.906 – 0.957). By multivariate analysis, positive biopsy core percentage ≥60%, and PI-RADS score ≥4 were independent factors for predicting EPE. The positive rate of EPE in lobes with zero, one and two factors (PI-RADS ≥4 and positive biopsy core percentage ≥60%) was 4%, 19%, and 38%, respectively. Conclusion: PPV and NPV of PI-RADS ≥4 for predicting pathologic EPE were 24.6% and 93.5%, respectively. PI-RADS ≥4 and positive biopsy core percentage ≥60% were independent risk factors for predicting EPE. The positive rate of EPE in lobes with zero, one and two factors (PI-RADS ≥4 and positive biopsy core percentage ≥60%) was 4%, 19%, and 38%, respectively.